2004
DOI: 10.1037/0278-7393.30.4.917
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Familiarity in Episodic Memory and Metamemory for Music.

Abstract: Participants heard music snippets of varying melodic and instrumental familiarity paired with animalname titles. They then recalled the target when given either the melody or the title as a cue, or they gave feeling-of-knowing (FOK) ratings. In general, recall for titles was better than it was for melodies, and recall was enhanced with increasing melodic familiarity of both the cues and the targets. Accuracy of FOK ratings, but not magnitude, also increased with increasing familiarity. Although similar ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Interestingly other memory studies have also found that expertise does not always ensure better performance (Korenman & Peynircioglu, 2004;McAuley, Stevens, & Humphreys, 2004). Korenman and Peynircioglu (2004) found that musically knowledgeable participants actually performed worse on a memory task involving familiar music with novel titles.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly other memory studies have also found that expertise does not always ensure better performance (Korenman & Peynircioglu, 2004;McAuley, Stevens, & Humphreys, 2004). Korenman and Peynircioglu (2004) found that musically knowledgeable participants actually performed worse on a memory task involving familiar music with novel titles.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to Lampinen et al's (2005) notion that memory involves the recollection of the perceptual, contextual, emotional, and cognitive features of the original place or event, music that was listened to in previous seasons may have been recalled and associated with the season. Korenman and Peynircioglu (2004) and Dalgleish et al (2001) have found that listening to music can often cue the recollection of episodic memory and metamemory of a stimulus that was present at the same time; thus associating positive and negative memories with specific seasons. Listening to a simple compellation of musical instruments or insightful lyrics in a favorite song could conjure memories of a certain time or place in which that song is most readily associated with.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…This hypothesis extends the view that the inhibitory effect is stored in memory representations (e.g., visual spatial working memory, as suggested by Castel, Pratt, & Craik, 2003) by emphasizing that representation stability can affect the duration of IOR. The memory research literature has indicated that episodic memory for familiar stimuli was better than that for novel stimuli (Korenman & Peynircioǧlu, 2004) and that shortterm memory span was larger when familiar words were to be remembered rather than unfamiliar words (Hulme, Maughan, & Brown, 1991). We postulated in a representation durability hypothesis that stimulus repetition stabilizes memory representation of the inhibitory effect.…”
mentioning
confidence: 88%